Clinical and laboratory profile and its outcome in scrub typhus-positive acute febrile illness cases in the Pediatric Department of BRD Medical College, Gorakhpur - Anamika Chaudhary; Bhoopendra Sharma; Ashok Kumar Pandey; Priyanka Singh (Indian Journal of Community and Family Medicine)
Background: A common cause of acute febrile illness in India is scrub typhus, a zoonosis caused by Orientia tsutsugamushi. It is a reemerging cause of acute undifferentiated fever in India and around the world. It was previously thought to be a seasonal disease occurring mainly in rural areas, but cases are now frequently detected in urban areas outside the monsoon season. This study determined the prevalence of scrub typhus and investigated the clinical and laboratory characteristics of scrub typhus-positive AFI cases and their outcomes. Material and Methods: The hospital based cross-sectional study included rapid tests for malaria parasites, scrub typhus immunoglobulin M (IgM) (enzyme-linked immunosorbent assay), typhoid IgM, and dengue IgM. Patients underwent the required investigations, such as cerebrospinal fluid examination. Results: Seventy-two (37.1%) of the 194 AFI patients were scrub typhus positive. The male-to-female ratio was 0.8:1. The most common symptom among the 72 scrub typhus-positive AFI patients was loose stools (61.1%), followed by vomiting (59.7%), abdominal pain (52.8%), headache (30.6%), swelling (13.9%), cramps (13.9%), and rash (11.1%). About 69.7% of rural land is scrub typhus positive. Fifty-four (75.0%) patients had thrombocytopenia, whereas hyperbilirubinemia was noted in 7 (9.7%) cases. Impaired renal function was noted in 9 (12.5%) cases. Hypocalcemia was reported in 25 (36.7%) patients, hyponatremia in 40 (55.6%) cases, and hypokalemia in 2 (2.8%) cases. Conclusion: Scrub typhus is common, accounting for a third of AFI cases. It is more common in rural and female-dominated areas. A child admitted with AFI with hepatosplenomegaly, lymphadenopathy, and anemia with thrombocytopenia must be evaluated for scrub typhus.